Feto-fetal transfusion syndrome. Issue 10 (October 1982) - Galea, P; Scott, J M; Goel, K M
Abstract : Out of 42 pairs of liveborn monochorial twins there were 32 pairs with vascular anastomoses. Of these, 11 pairs had feto-fetal transfusion syndrome. There were another 8 pairs of stillborn twin fetuses with vascular communications and in these chronic feto-fetal transfusion syndrome might have resulted in intrauterine death.